MANAJEMEN BISNIS RITEL DI KOTA MANADO PERSPEKTIF EKONOMI SYARIAH - Masrur, Masrur; Yusuf, Nasruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
A retail business is a series of product marketing that includes all activities that involve selling goods directly to end consumers as personal use items and is not a business. In order to be called a business that has Sharia standards, the entire business chain is sourced from provisions permitted by Sharia which include the capital cultivated, goods traded and services provided. This research examines the retail business management of Tokomu in Manado City which is owned by a devout Muslim entrepreneur so the research question is whether the retail business management that it runs will also be directly in accordance with Sharia economic provisions or standards. This research is descriptive-qualitative research in which the data were obtained from interviews, observations, and documentation. This research was conducted in the city of Mando with the main sample being Tokomu Manado. And from the research results it is known that Takomu, which was founded in 2017, is a type of independent retail business in which all forms of major decision-making are taken by the company owner, from procuring capital, selecting the type of goods, and estimating the value of the expected profit. The existing management structure, in the areas of purchasing, marketing and accounting, only provides input and consideration for company owners. In addition, the retail management of Tokomu's business has not yet fully implemented the Islamic retail business because the capital and goods sold are still mixed with capital and goods. who do not have sharia standards. Meanwhile, in terms of service and workforce management, it has complied with sharia provisions. Because the entire contract is transparent and clear, and nothing is usury, gharar, and maysir.